DIMENSION OF WHISTLEBLOWING SYSTEM: URGENSITY OF LEGISLATION STRENGTHENING - Bobby Briando; Sri Kuncoro Bawono; Tony Mirwanto (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2019)
Eradication of corruption in Indonesia is still the main agenda of the government in building good governance. One method to expose corruption is to use a whistleblower role that can help find the criminal mode of corruption. Whistleblower mechanism is divided into three main dimensions: Human, Structure and Process. But in practice whistleblower reporters in corruption cases in Indonesia have not received maximum legal protection. In Indonesia the normative regulation governing pursuant to Law No.13 of 2006 concerning Witness and Victim Protection as well as Supreme Court Circular Letter (SEMA) No.4 Year 2011 on Treatment of Criminal Reporting and Witness of Actors Cooperation The results show that from three dimensions of whistleblower system still does not yet have binding legislation. Whistleblower reporters only accept lightening relief. Specific whistleblower legislation is urgent. In legislation, at least, it should be in accordance with Whistleblower's protection.